2021
DOI: 10.1126/science.abf0998
|View full text |Cite
|
Sign up to set email alerts
|

Mapping out a future for ungulate migrations

Abstract: Limited mapping of migrations hampers conservation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 18 publications
1
72
0
Order By: Relevance
“…Our study adds caribou to the growing list of ungulates that exhibit individual-level migratory plasticity [ 18 , 19 , 97 101 ]. New efforts to map ungulate migrations seek to increase awareness of the threats to ungulate migration and to provide data to support their conservation and management [ 102 ]. Understanding dynamics of migratory behavior, destination, and timing plays an important role in supporting such goals.…”
Section: Discussionmentioning
confidence: 99%
“…Our study adds caribou to the growing list of ungulates that exhibit individual-level migratory plasticity [ 18 , 19 , 97 101 ]. New efforts to map ungulate migrations seek to increase awareness of the threats to ungulate migration and to provide data to support their conservation and management [ 102 ]. Understanding dynamics of migratory behavior, destination, and timing plays an important role in supporting such goals.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid environmental change, both global warming and increased anthropogenic development, is causing severe and dramatic impacts to the widespread and generally successful strategy of seasonal migration for many taxa, and the fate of many animal migrations is a topic of increasing concern (Wilcove and Wikelski, 2008;Kauffman et al, 2021). The ability of animals to respond to these changes depends deeply on their behavioral plasticity and cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, the question of whether migratory animals are more or less resilient to environmental disruptions in the environment remains open and largely case-specific (Moore and Huntington, 2008;Hardesty-Moore et al, 2018;Xu et al, 2021). On the one hand, migratory species may be more vulnerable as disruptions in either of the seasonal ranges or along a migratory corridor can have significant negative impacts (Wilcove and Wikelski, 2008;Seebacher and Post, 2015;Kauffman et al, 2021). On the other hand, migratory species might be more resilient due to their general wide-ranging mobility (Robinson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that lowdensity counterurbanization can have positive effects on animal biodiversity (insects, birds and mammals), especially when there is a newcomer attitude toward conservation (Hansen et al 2005;Bock and Bock 2009), although their species composition differs from natural environments with a high proportion of urban adapted species (Suarez-Rubio et al 2011). Also, certain negative outcomes for wildlife, such as disease transmission by domestic animals, or reduction of top carnivore and ungulate populations due to fences and roads could also occur (Hansen et al 2005;Kauffman et al 2021).…”
Section: Biodiversity and Ecosystem Servicesmentioning
confidence: 99%